PENGEMBANGAN MODEL STRATEGI BERSAING BERBASIS THE NEW 7-Ss SEKOLAH MENENGAH ATAS SWASTA DI KOTA SALATIGA - Leatomu, Lowisye; Ismanto, Bambang (Universitas Kristen Satya Wacana, 2016)
This study aimed to develop a competitive strategy development model based on the new 7SsÂ inÂ Satya Wacana Christian High School (SMA Lab) Salatiga. Tthis study is research and development, where the study was performed only at the fifth stage, the potential and problems, data collection, product design, design validation, and revision of the design. This research was conducted in Satya Wacana Christian High School (SMA Lab) Salatiga. Interviews were conducted with principal, vice principals curriculum, student section, public relations, teachers, administration of the employees, students and parents to know the framework of the new strategy 7-Ss on Satya Wacana Christian High School. While study documentation was conducted to determine the profile of the school, student profile, the work program of principals, vice-principals work program of curriculum, student affairs, and public relations. After the data collected, then the data was reduced, summarized, categorized, synthesized and presented in narrative form and tables. Model-based development ofÂ competitive strategy the new 7-Ss on Satya Wacana Christian High School consists of four rare developments, the formation of the team, defining the vision and mission, the analysis of the new 7-Ss, and strategy development. Formulation of a strategy based on the analysis of the new 7-Ss on Satya Wacana Christian High School consisted of three frameworks, namely Superior Stakeholder Satisfaction which includes the satisfaction of customers and workers, positioning program, and strategic cooperative.